From strong guanxi to weak guanxi: Connectivity in Chinese micro-charity. (July 2017) - Lin, Xun; Huang, Hua
Charity in China is deeply rooted in the guanxi tradition and mainly involves strong ties. In the wake of emerging social media, online charity (also known as micro-charity) has become increasingly popular over the past few years. People's participation in micro-charity is afforded by the ubiquitous connectivity of social media. Their charitable behaviours are steered towards connecting, communicating, and eventually contributing to the formation of a powerful digital environment, which essentially diffuses the awareness of responsibility and commitment. Thus, the affordance of connectivity makes it possible for Chinese people to break from the traditional tightly-bounded close ties towards loosely-bounded networks in micro-charity. In addition, by drawing on some college students' experiences, this article indicates that connectivity affords people's active engagement with micro-charity, which in turn fosters their distinct subjectivity pertaining to a social life that is intertwined with new media technology.